Safety of livestock products of bulls on various diets during fattening in the conditions of radioactive contamination - Savchuk, I.; Skydan, O.; Stepanenko, V.; Kryvyi, M.; KovalоvaS. (Regulatory Mechanisms in Biosystems, 2021)
Production of high-quality and safe food products in the conditions of technogenic environmental pollution is a problem worldwide, especially in Ukraine. As a result of the disaster at the Chornobyl Atomic Power Plant, radioactive substances, including caesium-137, contaminated the soil not only in Ukraine, but in many other countries. Zhytomyr Oblast is the fifth largest oblast in Ukraine and one of the regions that were the most damaged by the accident. Furthermore, this territory is contaminated by the most toxic heavy metals – lead (Pb) and cadmium (Cd) that actively migrate in the biological system: soil→ plant → animal → production → human, intensely accumulating in the products of plant and animal origin. The complex ecological situation and broad spectrum of biological and toxic actions of 137Cs, Pb, Cd require a number of measures that would prevent transformation of radioactive elements and heavy metals in the organism of animals, increase animals` productivity and safety of the food products made in the conditions of the Ukrainian Polisia. Therefore, we aimed at substantiating the practicability of using silage-concentrate, silage-concentrate-root vegetable and silage-concentrate-hay types of diet for young cattle during fattening and determining the impact of accumulation of 137Сs, Pb and Cd in livestock products. To perform the studies, we formed three groups of young bulls of Ukrainian Black Pied cattle using the method of analogues with creating comfortable maintenance condition and organization of in-detail planned feeding. The diet was composed of fodders prepared in the conditions of radioactive contamination. The laboratory surveys indicated that the main sources of 137Cs ingress in the organism of the animals were roughages and various types of silages, and the sources of heavy metals Pb and Cd were hay of red clover and concentrated fodders. In the experimental studies, we determined absolute and average daily weight gains, expenditures of metabolic energy per 1 kg of weight increment, specific activity of 137Сs and concentrations of the heavy metals (Pb and Cd) in the biological system “fodder-animal-production” during feeding of bulls with various-type diets in the conditions of the III zone of radioactive pollution. It was confirmed that substituting maize silage and carbohydrate fodders increased the average daily gains in the live weight by 2.3–4.6%, decreased specific activity of 137Cs by 8.7–20.1%, the content of Pb by 36.2%, Cd by 34.1–66.7% in the longissimus at silage-concentrate-root vegetable and silage-concentrate-hay types of diet for bulls. Thus, use of silage-concentrate-root vegetable and silage-concentrate-hay types of diets compared with silage-concentrate feeding had a positive effect on their productivity and safety of the food production.